Appréhender les vulnérabilités en santé au Brésil : Usages pluriels de la photographie - Rougeon, Marina; Trad, Leny; Assis Brasil, Sandra; Mara Dias Gomes, Thais; Mezza, Martin (Anthropologica, 2022)
This essay sheds light on the multitude of ways in which photography can be used to research health and vulnerabilities by drawing upon three research projects conducted in Brazil. In the first research project, photography is a documentary source used to explore the definitions of insanity and normalcy in the context of psychiatric clinics throughout different periods, and to capture more recent local creative experiences in the context of the Brazilian psychiatric reform. Then, on the basis of an account consisting of choreographic images of bodies who work in tidal waters, photography allows readers to broaden their understanding of the daily work of island shellfish harvesters. Lastly, we share the experiences of an action research project that organized self-portrait workshops for Black youth living in a workingclass district of Salvador, to promote healthy physical and sexual practices and ethnic-racial and gender-based empowerment. By taking a careful look at groups subject to social invisibility, vulnerability or a certain degree of stigmatization, these projects uncover social and political inequalities that have been shaped by history. These echoed experiences enhance the heuristic and sensitive dimensions of photography, whose place in research contributes towards preserving the ability to imagine and create, so necessary to moving beyond the methodological imitation that is captured in the production of knowledge.